1987
DOI: 10.1038/eye.1987.72
|View full text |Cite
|
Sign up to set email alerts
|

Air, methylcellulose, sodium hyaluronate and the corneal endothelium. Endothelial protective agents

Abstract: In a randomised trial the endothelial protective agent used during extracapsular cataract extraction and intraocular lens insertion was air in 19 eyes (group 1), methylcellulose in 25 eyes (group 2) and sodium hyaluronate in 22 (group 3). The cell population densities of each eye were estimated immediately before and three months after the operations to determine the degree of cell loss. Eyes showing mechanical (touch) damage on the second postoperative day were eliminated. The numbers of eyes in each group wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…There are no studies to this point regarding the minimum size of the initial air bubble after DMEK surgery for the graft to remain attached, whereas a larger bubble after DMEK and Descemet stripping automated endothelial keratoplasty might correspond with an increased risk of developing pupillary block 6 or increased loss of endothelial cells. [16][17][18] Reports of incidence of pupillary block after DMEK range from 0% to 11.5% (literature summary in Table 1). Thus, the goal of this study was to retrospectively analyze the outcomes of smaller and larger post-DMEK air bubbles of 50% and 80% of the ACV, respectively, regarding graft adherence, endothelial cell loss, and rates of pupillary block.…”
mentioning
confidence: 99%
“…There are no studies to this point regarding the minimum size of the initial air bubble after DMEK surgery for the graft to remain attached, whereas a larger bubble after DMEK and Descemet stripping automated endothelial keratoplasty might correspond with an increased risk of developing pupillary block 6 or increased loss of endothelial cells. [16][17][18] Reports of incidence of pupillary block after DMEK range from 0% to 11.5% (literature summary in Table 1). Thus, the goal of this study was to retrospectively analyze the outcomes of smaller and larger post-DMEK air bubbles of 50% and 80% of the ACV, respectively, regarding graft adherence, endothelial cell loss, and rates of pupillary block.…”
mentioning
confidence: 99%
“…Further SM studies showed that each was as good as the other in protecting the endothelium from mechanical touch damage during IOL insertion and that neither, unlike air in the anterior chamber, embarrassed the delicate cells. 42 In many of the IOL studies, cataract extraction without an IOL served as the control, and some interesting observations ensued. For example it was found that the endothelium of the aphakic eye loses cells with ageing faster than in normal eyes.…”
Section: The Endothelium In Diseasementioning
confidence: 99%
“…However, a number of researchers reported that the type of the viscoelastic agent is also important to prevent corneal endothelial damage [6][7][8]. Although the viscoelastic agents mostly overcome the toxic effect on corneal endothelium, introducing small and larger air bubbles into anterior chamber may be inevitable around an incision or through processing a phacoemulsification stage for a dense cataract or during vitreal fluid-air exchange in a pars plana vitrectomy procedure [5,9,10]. This article reviews the corneal endothelial damage by air bubbles and prevention ways of this problem during intraocular surgeries.…”
Section: Introductionmentioning
confidence: 99%